The Interactive Effects Of Human Capital, Structural Capital And Social Capital On Firm Performance - Wan Yusof, Wan Fadzilah; Muhamad Jantan, Muhamad Jantan; Ibrahim, Daing Nasir (Asian Academy of Management (AAM), 2004)
Independent studies conducted on the impact of human capital, structural capital and social capital on firm performance have shown that a significant positive relationship can be established between each of them and performance. This study examined if each of these components of intellectual capital would show more significant relationships if they were to interact with each other, whether in a two-way or three-way interactions. Results provided by a sample collected from 298 business units of firms in the Malaysian financial services industry is consistent with the suggestion that the key driving forces in the contemporary business environment has moved from the management of tangible resources to the exploitation of intangible resources and differential outcome can be expected from the interactive nature of the components.